Convolution-based modelling of the stimulus modulation broadening in derivative spectroscopy - Konowalczyk, M; Konowalczyk, M; Foster Vander Elst, O; Storey, J (University of Oxford, 2020)
This dataset contains the supplementary data to the manuscript under the name "Development of lock-in based overtone Modulated MARY spectroscopy for detection of weak magnetic field effects", as well as demonstration and data analysis scripts.